A software player for providing hints in problem-based learning according to a new specification - Muñoz-Merino, Pedro J.; Delgado Kloos, Carlos (Computer applications in engineering education, 2009)
The provision of hints during problem solving has been a successful strategy in the learning process. There exist several computer systems that provide hints to students during problem solving, covering some specific issues of hinting. This article presents a novel software player module for providing hints in problem‐based learning. We have implemented it into the XTutor Intelligent Tutoring System using its XDOC extension mechanism and the Python programming language. This player includes some of the functionalities that are present in different state‐of‐the‐art systems, and also other new relevant functionalities based on our own ideas and teaching experience. The article explains each feature for providing hints and it also gives a pedagogical justification or explanation. We have created an XML binding, so any combination of the model hints functionalities can be expressed as an XML instance, enabling interoperability and reusability. The implemented player tool together with the XTutor server‐side XDOC processor can interpret and run XML files according to this newly defined hints specification. Finally, the article presents several running examples of use of the tool, the subjects where it is in use, and results that lead to the conclusion of the positive impact of this hints tool in the learning process based on quantitative and qualitative analysis. © 2009 Wiley Periodicals, Inc. Comput Appl Eng Educ 17: 272–284, 2009; Published online in Wiley InterScience (www.interscience.wiley.com); DOI 10.1002/cae.20240